ANALYSIS OF THE VISIT RATE AT THE IRIAN MARELAN SUPERMARKET DURING THE COVID-19 PANDEMIC - Kartika , Dinda; Lubis, Riri Syafitri; Widyasari, Rina (Pena Cendekia Insani, 2021)
Currently our country is experiencing a disaster due to a very dangerous virus that has claimed many lives or commonly referred to as COVID-19. The government had limited the operating hours of public places to prevent the spread of the virus. This has resulted in disruption of economic activities, one of which is the Irian Supermarket & Dept Store. This research was conducted to determine how the level of visits to Irian with the Spearman Rank Correlation method. From the results of the Spearman Rank correlation analysis carried out, the calculated value is 0.307 with a positive sign which indicates a low level of relationship and it is concluded that the level of visits is not influenced by the application of health protocols but is influenced by facilities and sales techniques, This can also be seen in the results of the t-test. The result of count obtained is 3.20 shows that the variable level of visits has a significant correlation with purchasing decisions.